Genome-Wide Association Study Reveals a New QTL for Salinity Tolerance in Barley (Hordeum vulgare L.) - Fan, Yun; Zhou, Gaofeng; Shabala, Sergey; Chen, Zhong-Hua; Cai, Shengguan; Li, Chengdao; Zhou, Meixue (Frontiers in Plant Science, 2016)
Salinity stress is one of the most severe abiotic stresses that affect agricultural production. Genome wide association study (GWAS) has been widely used to detect genetic variations in extensive natural accessions with more recombination and higher resolution. In this study, 206 barley accessions collected worldwide were genotyped with 408 Diversity Arrays Technology (DArT) markers and evaluated for salinity stress tolerance using salinity tolerance score – a reliable trait developed in our previous work. GWAS for salinity tolerance had been conducted through a general linkage model (GLM) and a mixed linkage model (MLM) based on population structure and kinship. A total of 24 significant marker-trait associations were identified. A QTL on 4H with the nearest marker of bpb-9668 was consistently detected in all different methods. This QTL has not been reported before and is worth to be further confirmed with bi-parental population.